Peran Produser Dalam Produksi Web Series “Gara-Gara Gadget” - Rahmadani, Nadea; Eriend, Dion (CV. ITTC INDONESIA, 2024)
Web series or web series are short series video shows, can be in the form of series films, tutorials, news information, tips, tricks, and so on that are made specifically for online consumption. Currently, there is a lot of entertainment in the form of videos that can be found in the internet world, including YouTube. Behind the production of web series, of course, it is inseparable from many workers who are able to unite their creative minds to produce a web series. So, the author carries out the Final Project of this web series as a producer. The producer is the person who is responsible and leads the process of creating a web series, from the pre-production stage, the production stage to the post-production stage. At the time of preparation, the producer manages all planning from determining the schedule, organizing the team, finance, managing the time and as a source of information. During production, the producer supervises the shooting so that the production is in accordance with the plan as well as a decision maker when there are problems outside of planning. During post-production, the producer will oversee the editing process with the director. To become a producer is not only a person who has money for film production funding, because if so, people who have money can become producers And the producer's role in the production of the web series or web series